The Representation of Beautiful Women in Skin-Whitening Cosmetics TV Commercials - Pradetya Novitri (Universitas Pendidikan Indonesia (UPI), 2014)
Realizing the true intention of the message the media convey becomes important since sometimes the message is hidden behind the text. Today advertisement of skin-whitening cosmetics has changed the way people consider about beautiful women. Therefore, this research is aimed at finding how beautiful women are represented in skin-whitening TV commercials. The study uses descriptive analysis which is qualitative in nature. Employing visual grammar framework as proposed by Kress and van Leeuwen (2006) and the concept of second order of signification by Barthes (1957), the study analyzes pictures and narrations/dialogues contained in three skin-whitening cosmetics TV commercials. The study found that beautiful women represented as confident, powerful, have good personalities, modern, women’s best friend and object of attraction.Keyword: advertising, TV commercial, representation, construction, skin-whitening cosmetics